EDUKASI PEMAHAMAN KEPEMIMPINAN DAN JOB DESCRIPTION PADA PERANGKAT NAGARI KOTO LAWEH - Siska Yulia Defitri; Esi Sriyanti; Netti Indrawati; Afni Yeni; Nurhayati Nurhayati (JURNAL PENGABDIAN MANDIRI, 2022)
One type of organization is service, especially government agencies that have the function of providing services to the community. The function of government employees in providing service is important in accordance with the duties and positions they have which are stated in their job descriptions. However , this job description can not run well if it is not coordinated by the leadership who can direct his employees in carrying out their duties and responsibilities properly . This service is carried out at the Office of the Mayor of Nagari Koto Laweh, Solok Regency by providing education and understanding of the functions and roles of carrying out duties properly in accordance with their respective job descriptions. The service is carried out through lectures and discussions with a continuous plan on a regular basis